Retrofit of an orthotropic steel deck with compact reinforced reactive powder concrete. Issue 3 (3rd March 2016) - Cao, Junhui; Shao, Xudong; Zhang, Zhe; Zhao, Hua
Abstract : Compact reinforced reactive powder concrete (CRRPC) was proposed to retrofit deteriorated asphalt overlays and to strengthen orthotropic steel deck (OSD) bridges. The resultant OSD-CRRPC composite deck is also referred to as a light-weight composite deck (LWCD) system. This paper provides experiences and lessons learned from the first application of CRRPC to retrofit the deficient asphalt overlay of an existing steel bridge in China. The paper includes information relating to finite element (FE) model analyses, a fatigue loading test, construction processes and a field measurement. FE analyses revealed that a 50-mm CRRPC layer decreased the vehicle-induced stresses in the OSD by 34–83% relative to an OSD with an 80-mm asphalt overlay. As a result, the fatigue life of the OSD could be extended significantly. The static and fatigue safeties of CRRPC were proved by comparing the predicted and experimental stresses, and field construction demonstrated the feasibility of the proposed system. CRRPC developed no shrinkage cracks after hot-steam treatment in field application. In addition, a field measurement verified that CRRPC outperformed an asphalt overlay in reducing the vehicle-induced stresses in the OSD. The results demonstrate the safety and feasibility of retrofitting and strengthening OSD bridges with CRRPC.